1959
DOI: 10.1111/j.1550-7408.1959.tb04364.x
|View full text |Cite
|
Sign up to set email alerts
|

The Invasion of the Cecal Mucosa by Eimeria tenella sporozoites and their Transport by Macrophages*

Abstract: SYNOPSIS. The establishment of Eimeria tenella sporozoites in the cecal mucosa of the chicken is described. The invasion process was similar to that reported for E. necatrix by Van Doorninck and Becker. Sporozoites were found to pass through the surface epithelium of the cecal mucosa into the lamina propria. Within the lamina propria the sporozoites were engulfed by macrophages and transported to the cells of the glands of Lieberkühn. Development of the sporozoites ensues within the gland epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

1964
1964
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…Challey and Burns (3) reported that invading E. tenella sporozoites are engulfed by macrophages in the lamina propria and are transported by them to mucosal cells of the ceca where the parasites initiate an infection. The experiments reported here were designed to investigate the association of sporozoites of E. tenella and macrophages obtained from immune and non-immune chickens and the effects of immune and non-immune serum on the sporozoite-macrophage association.…”
mentioning
confidence: 99%
“…Challey and Burns (3) reported that invading E. tenella sporozoites are engulfed by macrophages in the lamina propria and are transported by them to mucosal cells of the ceca where the parasites initiate an infection. The experiments reported here were designed to investigate the association of sporozoites of E. tenella and macrophages obtained from immune and non-immune chickens and the effects of immune and non-immune serum on the sporozoite-macrophage association.…”
mentioning
confidence: 99%
“…Is it one that enters the glandular epithelium from the gland lumen, or is it one that passes through the lamina propria? Challey and Burns (2) and Van Doorninck and Becker(l3) supported the view that the cycles of E . tenella and E .…”
Section: Discussionmentioning
confidence: 87%
“…However, there are several differences concerning the speed with which sporozoites were transported to the gland and whether they were free or associated with a macrophage. Challey and Burns (2) found no E . tenella sporozoites in the lamina propria at 48 hr and Pattillo(l0) found none there at 38 and 54 hr.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The finding of sporozoites in intraepithelial leukocytes (IEL) deep in the crypts of Lieberkiihn indicate that E. mitis uses transport host cells to reach the crypts as do E. tenella, E. necatrix, and E. acervulina (2,3,10,18,22). No development like that of E. dispersa in the turkey (1 5) occurred in IEL's with E .…”
Section: Discussionmentioning
confidence: 99%